Cytogenetic Key to Identification of Triatominae Species Reported in an Outbreak Region of Oral Transmission of Chagas Disease in the Brazilian Northeast - Nhapulo, Emercio Felisberto; de Mello, Denis Vinícius [UNESP]; Cesaretto, Laura Poloto [UNESP]; Alevi, Julia Junqueira [UNESP]; Cristal, Daniel Cesaretto [UNESP]; Montanari, Giulia [UNESP]; Azevedo, Luísa Martins Sensato [UNESP]; Masarin, Isabella da Silva [UNESP]; Galvão, Cleber; Alevi, Kaio Cesar Chaboli [UNESP] (American Society of Tropical Medicine and Hygiene, 2023)
Oral transmission from the consumption of processed food with triatomines and/or their feces infected with Trypanosoma cruzi prevails among recent cases of Chagas disease in Brazil. In Paraíba, a state of the Brazilian northeast, there was an outbreak caused by the consumption of sugarcane juice that resulted in 26 cases of infection and one death. Until now, 10 species of triatomines have been reported in this Brazilian state. Thus, we developed a dichotomous key to assist in the correct identification of Paraíba triatomines based on cytogenetic data. The dichotomous key allowed the differentiation of all the species in this state. Although the purpose of CytoKeys is not to replace dichotomous keys based on morphological data, the use of these complementary keys can help to solve taxonomic problems, preventing identification errors, especially between similar species such as Triatoma brasiliensis and Triatoma petrocchiae, both present in the Brazilian northeast.